A pilot study investigating the rapid estimation of intact dry density of chalk using low impact energy hardness measurements taken with an Equotip Leeb hardness tester. Issue 2 (2022) - Thrower*, Andrew; Barlow, John; Moore, Roger; Cane, Tim
No abstract available